2007
DOI: 10.22495/cocv5i1c4p2
|View full text |Cite
|
Sign up to set email alerts
|

Boards and diversification strategy: evidence from the Spanish savings banks sector

Abstract: When executives seek to satisfy their need for prestige and status through long-term strategic decisions that increase the size of the company -such as corporate diversification- but do not improve the firm’s performance, agency costs might appear. Thus, the current work aims to responding the following question: does the corporate governance of an organization influence its diversification strategy? Considering that most research to date has focused on the governance structure of large public limited companie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…On the other hand, previous studies claim that the advantages of larger boards are related to their greater heterogeneity (Dharmadasa et al, 2014;Guest, 2009), which can provide firms with more comprehensive advice, better-informed monitoring and better external linkages; thus, improving growth strategy options evaluation and implementation (Zheng and Tsai, 2019). Consistently, most previous studies suggest that the greater the number of directors, the greater the opportunities to implement diversification moves (Garcı ´a Soto and A ´lamo Vera, 2007;Marouan, 2015), consistent with findings reporting that more diversified companies tend to have a higher number of outside directors (Anderson et al, 2000) that can provide firms with a better access to external resources.…”
Section: The Role Of Board Sizesupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, previous studies claim that the advantages of larger boards are related to their greater heterogeneity (Dharmadasa et al, 2014;Guest, 2009), which can provide firms with more comprehensive advice, better-informed monitoring and better external linkages; thus, improving growth strategy options evaluation and implementation (Zheng and Tsai, 2019). Consistently, most previous studies suggest that the greater the number of directors, the greater the opportunities to implement diversification moves (Garcı ´a Soto and A ´lamo Vera, 2007;Marouan, 2015), consistent with findings reporting that more diversified companies tend to have a higher number of outside directors (Anderson et al, 2000) that can provide firms with a better access to external resources.…”
Section: The Role Of Board Sizesupporting
confidence: 87%
“…At the corporate strategy level, the diversification decision is one of the riskiest and most important. In the specific context of family business, such a decision represents a fertile area of inquiry (Garcı ´a Soto and A ´lamo Vera, 2007;G omez-Mejı ´a et al, 2010) that, despite receiving little empirical attention over the years with only a few notable exceptions (Anderson and Reeb, 2003), has recently seen a revived academic interest (Hafner, 2021). Indeed, diversification is controversial for family firms because it highlights the potential mismatch among their multiple objectives (Mun ˜oz-Bullon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As regards to the directors’ board variables, Jensen and Meckling (1976) believe that a large board of directors is generally less effective than a small size as it favors the dominance and the enlargement of the discretionary power. A study conducted by Garcia-Soto and Alamo-Vera (2007), dealing with the factors that influence the diversification strategy in the Spanish banks, found that board size is positively associated with diversification. According to Chenini and Jarboui (2016), the presence of foreign directors may help banks to facilitate their access in capital markets to grow, diversify their investments and offer their products to foreign customers.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%